1992
DOI: 10.1080/02626669209492570
|View full text |Cite
|
Sign up to set email alerts
|

An effective scale-dependent dispersivity deduced from a purely convective flow field

Abstract: In the case of straight flow but with hydraulic conductivity varying in a transverse direction, the distribution of hydraulic conductivity has been determined for which the breakthrough curve due to convection only will have the same analytical form as the onedimensional convection/dispersion equation solution at the outlet end of a porous medium. That distribution is found exactly and it is very similar to the lognormal distribution. This result is significant since field evidence indicates that the logarithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This is equivalent to the concept of heterogeneous advection used by Becker and Shapiro (2003) to describe mass spreading related to separation of advective pathways (Berkowitz et al 2006). The scaling of dispersive properties has also been interpreted as a consequence of the use of a n-1 dimension analytical solution to a n-dimension problem (Pickens andGrisak 1981)-Morel-Seytoux andNachabe (1992) demonstrated that for permanent flow conditions with pure advection in 2D that an equivalent one-dimensional (1D) macro-dispersivity transport scheme can be used with a dispersivity that will be a linear function of the scale. This work introduces a proportionality factor between macroscopic dispersivity and scale, which was also used by Pickens and Grisak (1981) for well-to-well tracer tests performed in a sandy stratified aquifer.…”
Section: Dispersivity As a Linear Function Of The Scalementioning
confidence: 99%
“…This is equivalent to the concept of heterogeneous advection used by Becker and Shapiro (2003) to describe mass spreading related to separation of advective pathways (Berkowitz et al 2006). The scaling of dispersive properties has also been interpreted as a consequence of the use of a n-1 dimension analytical solution to a n-dimension problem (Pickens andGrisak 1981)-Morel-Seytoux andNachabe (1992) demonstrated that for permanent flow conditions with pure advection in 2D that an equivalent one-dimensional (1D) macro-dispersivity transport scheme can be used with a dispersivity that will be a linear function of the scale. This work introduces a proportionality factor between macroscopic dispersivity and scale, which was also used by Pickens and Grisak (1981) for well-to-well tracer tests performed in a sandy stratified aquifer.…”
Section: Dispersivity As a Linear Function Of The Scalementioning
confidence: 99%
“…Simple analytical solutions for transient regimes (of plug or periodic type) with explicit expressions for the Hamiltonian (stream function \\i (x, y, t)) of the system of order 3/2 can serve as test procedures for more realistic models involving dissipation (compressible matrix or fluid). The phenomenon of dispersion is usually related with aquifer inhomogeneity and parameters of the advective dispersion equation are connected with purely convective flow and conductivity distributions (Morel-Seytoux & Nachabe, 1992). Meanwhile transient fluctuations of a seepage flow seem to be able produce dispersion (or chaos) even in homogeneous porous media.…”
Section: Resultsmentioning
confidence: 99%